2017
DOI: 10.1039/c7nj01206c
|View full text |Cite
|
Sign up to set email alerts
|

The impact of aluminum impurity on the regenerated lithium nickel cobalt manganese oxide cathode materials from spent LIBs

Abstract: An effective recycling process from spent LIBs has been developed, and the tolerability of aluminum was studied in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Most technologies of recycling for spent LIBs have focused on the recycling of active materials such as LiCoO 2 , LiNiO 2 , and LiNi x Co y Mn z O 2 (NCM) because of their higher economic values. The cathode consists of active materials and minor amounts of carbon powder and polymer binder, all of which are coated on Al foil current collector by cohesive force of the polymer binder. Peeling cathode material from Al foil is an important step for the recycling of cathode active materials, as it eliminates interference of the Al element to the subsequent recycling procedures and the metal current collector can also be recovered.…”
Section: Introductionmentioning
confidence: 99%
“…Most technologies of recycling for spent LIBs have focused on the recycling of active materials such as LiCoO 2 , LiNiO 2 , and LiNi x Co y Mn z O 2 (NCM) because of their higher economic values. The cathode consists of active materials and minor amounts of carbon powder and polymer binder, all of which are coated on Al foil current collector by cohesive force of the polymer binder. Peeling cathode material from Al foil is an important step for the recycling of cathode active materials, as it eliminates interference of the Al element to the subsequent recycling procedures and the metal current collector can also be recovered.…”
Section: Introductionmentioning
confidence: 99%
“…Ren at al. studied the effect of Al impurities on the capacity of regenerated NMC cathodes [106], and concluded that no significant effect was observed when the molar ratio of Al/(Ni + Co + Mn) was below 3 to 100, but capacity could decrease by 40% if this threshold was exceeded. In addition to Al current collector dissolution, a pre-leaching step may be allowed to remove plated Cu contaminating Li-ion cathode.…”
Section: Removal Of Current Collector and Bindermentioning
confidence: 99%
“…Ren et al [82] revealed the effect of Al impurity on the regenerated NCM material from its electrochemical performance. Ren et al [82] revealed the effect of Al impurity on the regenerated NCM material from its electrochemical performance.…”
Section: Resynthesis Of Ncmmentioning
confidence: 99%
“…It should be noted that the impurities like Al may exist in these type of processes during their separation from cathode material and would affect the material performance when increase to a certain level. Ren et al revealed the effect of Al impurity on the regenerated NCM material from its electrochemical performance. Li[(Ni 1/3 Co 1/3 Mn 1/3 ) 1− x Al x ]O 2 has been synthesized with the different amount of Al 2 (SO 4 ) 3 with respect to other metal ions in the leachate by means of solid‐state synthesis.…”
Section: Spent Materials In Libsmentioning
confidence: 99%